The effects of thermal history on tensile properties of poly (vinyl chloride) and its composite with sugarcane bagasse. - Salit, Mohd Sapuan; Abdan, Khalina; Yunus, Robiah; Wirawan, Riza (2011)
Composites of sugarcane bagasse in poly(vinyl chloride) (PVC) matrix were produced by a compression molding method followed by various heat treatment processes, involving slow cooling (annealing), fast cooling (quenching), and re-heating to a temperature below Tg. The effects of the thermal history were examined by the measurement of tensile strength and elongation at break as well as by differential scanning calorimetry. It was observed that the heat treatments affected the elongation at break of unfilled PVC significantly with less significant effect on the tensile strengths. In contrast, various tensile strengths of sugarcane bagasse PVC composites were observed after various heat treatments with less significant effect to the elongations at break. In addition, recycling of the composites may erase the effect of thermal history. Uniform tensile properties of the composites were achieved after recycling process.